Páramo de Belmira as an important centre of endemism in the northern Colombian Andes: new evidence from Pronophilina butterflies (Lepidoptera: Nymphalidae, Satyrinae, Satyrini) - Pyrcz, Tomasz W.; Clavijo, Alejandra; Uribe, Sandra; Marin, Mario A.; Alvarez, Carlos F.; Zubek, Anna (Zootaxa, 2016)
Páramo de Belmira (Páramo de Santa Inés) is the highest part of the Andean Central Cordillera in the Colombian department of Antioquia. It harbours a pocket of highlands grassland vegetation isolated from the nearest southerly other large paramo extensions by some 150 km. Butterflies sampling was carried out for over three years in the cloud forest–paramo mosaic and open grassland at 2650–3350 m. As a result, several new taxa of various butterflies groups were identified, including three species and two subspecies belonging to the Satyrinae subtribe Pronophilina, described herein: Lymanopoda casneri n. sp., L. ionius lilliput n. ssp., Panyapedaliodes rojasi n. sp., Pedaliodes nutabe n. sp. and Apexacuta orsedice mariadelmarae n. ssp. L. casneri is particularly interesting from the biogeographical perspective as its nearest relative is L. hazelana Brown, found in south–central Ecuador, some 1000 km southwards. Overall, 48 species of Pronophilina were identified. Considering the occurrence of several endemic species and subspecies of butterflies in the extremely restricted paramo grasslands in the study area, and the anthropogenic pressure from surrounding locations, it is worth attributing the Páramo de Belmira a protection area status.